Applying a Constructivist Learning Approach in Designing Educational Games to Enhance Conceptual Understanding of Geometric Shapes - Muhammad Rizki Arzi; Putri Ayu Andini; Manda Apriliani Fadzillah; Alya Andini Prasetyo; Ahmad Zulfi'Azwan Nur; Okta Purnawirawan (Faculty of Computer Science (FILKOM) Brawijaya University, 2026)
Mathematics instruction on plane figures still faces challenges in the form of students’ low conceptual understanding and a limited availability of interactive learning media. This study aims to develop MathMind, an educational game based on Game-Based Learning with a constructivist approach, to improve students’ understanding of geometric concepts at SD Negeri 2 Pandanrejo. The study employed the Research and Development method using the ADDIE model. MathMind was developed as a level-based game featuring gamification elements such as rewards, timers, lives, and interactive feedback. Evaluation was conducted through expert validation, users response testing, and pretest posttest analyses using a paired-sample t-test. The results showed a validity rate of 96% from media experts and 98% from content experts, as well as a user response rate of 94%. The pretest and posttest results indicated a significant improvement in students’ conceptual understanding with a p-value < 0.001 and a high effect size. These results demonstrate that MathMind effectively enhances elementary school students’ engagement and understanding of plane figure concepts.